Healing at Home or Re‐Marginalisation? Perceived Neighbourhood Environment, Sense of Belonging and Mental Health of Return Migrants in Peri‐Urban China - Lingling Su; Enyu Chang (Population, Space and Place, 2026)
ABSTRACT Amidst China's transition into a new phase of urbanisation, the mental health of return migrants has emerged as a critical issue. Whether returning to rural communities offers the spiritual solace of ‘healing at home’ or precipitates a descent into ‘re‐marginalisation’ remains poorly understood, particularly in metropolitan peri‐urban villages where remembered hometowns are being reshaped by urbanisation. Drawing on the survey of return migrants in peri‐urban Zhengzhou, this study constructs and validates a moderated mediation model based on field survey data to systematically investigate the mechanisms underlying the impact of neighbourhood environmental perception on the mental health of returnees. The findings reveal that: (1) more favourable perceptions of both built and social neighbourhood environments were associated with fewer mental health problems, and perceived built environment was positively associated with perceived social environment; (2) multi‐scalar sense of belonging played a mediating role in the associations between perceived neighbourhood environments and mental health, with village belonging representing the more prominent mediating pathway and highlighting the role of emotional identification in return migrants' post‐return adaptation; and (3) migration experience moderated the association between village belonging and mental health: longer out‐migration duration attenuated the protective association of village belonging with mental health, whereas a higher host‐city tier and greater perceived social exclusion strengthened its negative association with mental health problems. This study uncovers the spatial‐emotional interactive mechanisms of psychological adaptation among return migrants, providing a robust theoretical basis and practical pathways for enhancing the mental health of returnee populations through the improvement of human settlements and community governance.